SEG Technical Program Expanded Abstracts 2006 2006
DOI: 10.1190/1.2369941
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐bed reflectivity inversion

Abstract: Thin-bed reflectivity inversion is a form of spectral inversion which produces sparse reflectivity estimates that resolve thin layers below the tuning thickness. The process differs from other inversions in that it is driven by geological rather than mathematical assumptions, and is based on aspects of the local frequency spectrum obtained using spectral decomposition of various types. The resolution of thin-bed reflectivity inversion is far superior to the input data and so makes it very suitable for characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…Partyka et al (1999), Partyka (2005), Marfurt and Kirlin (2001) also use spectral decomposition to predict the thickness of imaged sedimentary layers. While Chopra et al (2006) and Puryear and Castagna (2008) use spectral inversion for layer thickness determination. Adriansyah and McMechan (2002) detect thin reservoirs from attribute analysis, acoustic impedance inversion, and full-wavefield modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Partyka et al (1999), Partyka (2005), Marfurt and Kirlin (2001) also use spectral decomposition to predict the thickness of imaged sedimentary layers. While Chopra et al (2006) and Puryear and Castagna (2008) use spectral inversion for layer thickness determination. Adriansyah and McMechan (2002) detect thin reservoirs from attribute analysis, acoustic impedance inversion, and full-wavefield modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Portniaguine and Castagna (2004) used spectral decomposition of the data together with three different constraints (namely, the L1 norm, L2 norm, and sparse spike constraints) to prove the applicability of spectral decomposition as well as the higher resolution of results using the sparse spike constraint. Puryear (2006), Chopra et al (2006aChopra et al ( , 2006b, and Puryear and Castagna (2006) showed that the inversion of spectral decompositions for layer properties can be improved when the reflection coefficients are determined simultaneously, which is to say that the inversion should be launched on the reflectivity series instead of on the trace itself.…”
Section: Introductionmentioning
confidence: 96%
“…Variations in wave amplitude and phase, caused by layers of different thicknesses, jointly with interference patterns, allow the extraction of stratigraphic details such as thicknesses and lateral continuity (Partyka, 2005). Now, as it is unlikely for a lithological unit to have the same coefficients at its top and its base, the relevant pair of reflection coefficients r 1 and r 2 may be decomposed into an even part (r 1 + r 2 ) 2 ⁄ and an odd part (r 1 − r 2 ) 2 ⁄ (Castagna, 2004;Chopra, Castagna & Portniaguine, 2006). This results in the Spectral Inversion (Puryear & Castagna, 2008) that transforms the amplitude spectrum of a seismic trace estimated in a narrow window in a reflectivity series which depends on the thicknesses of layers in the window of analysis.…”
Section: Introductionmentioning
confidence: 99%